Effect of Power Ultrasound and Microstructure Change of Casein Micelle in Yoghurt - Tabatabaie, F.; Mortazavi, A.; Ebadi, A.G. (Asian Journal of Chemistry, 2010)
In present studies, the changes in micro structural of yoghurt casein micelles during application power ultrasound has been investigated. The gel structure of yoghurt contributes strongly to its characteristic texture which is an important organoleptic property perceived by the consumer and strongly dependent on the distribution of porosity in network of case gel. The experimental results demonstrated that the microstructure of ultrasound treated milk yoghurt for 0, 5, 10, 15, 20, 25 and 30 min at 20 KHz frequency, had more interconnected chains of regularly-shaped casein micelles, with reduced particle size as well as more spherical in shape, exhibiting a smooth more regular surface and presenting more uniform size distribution and more homogenous porosity. This work offer the power ultrasound improved the gel texture and useful in manufacturing process of yoghurt.